IMPLEMENTASI PENGHARMONISASIAN RANCANGAN PERATURAN DAERAH BERDASARKAN PERATURAN MENTERI HUKUM DAN HAM NOMOR 22 TAHUN 2018 - Iswahyudi, Fauzi; Nasution, Faisal Akbar; Suhaidi, Suhaidi; Agusmidah, Agusmidah (BULETIN KONSTITUSI, 2022)
The harmonization of draft regional regulations is part of the stages of drafting the formation of laws and regulations to harmonize the substance of the draft laws and regulations and adapt them to the techniques of drafting laws and regulations, as an effort to minimize the occurrence of cancellation or revocation of regional regulations due to disharmony with regulations. related legislation. The formulation of the problem that will be described in this paper is how to implement the harmonization of regional legal products based on the provisions of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 22 of 2018 concerning the Harmonization of Draft Laws and Regulations Formed in the Regions by the Designer of Legislation -Invitation. The method used in this research is a normative juridical research method. The results of the study indicate that in the process of forming regional regulations, they must go through the stages of harmonization by involving the drafting of laws and regulations. The results of the study show that there are still many regional regulations in the regions that have not gone through the harmonization stage, thus allowing the draft regional regulations that have been formed not to comply with the laws and regulations both formally and materially. Minister of Law and Human Rights Number 22 of 2018.